The grammatical status of –eykey and its implications on the syntax of Korean morphological passives - Park Myung-Kwan (De Gruyter, 2021)
This study investigates the grammatical status of the so-called Dative particle –eykey and its implications on the syntax of Korean morphological/lexical passives. We first argue that this type of passive derives from causative/experiential constructions in this language. The former and the latter involve the same form of verb, but in the process of passivization the null passive morphology on the embedded transitive verb phrase selected by the matrix causative/experiential morpheme demotes the Dative –eykey-marked Causee in embedded [Spec, VoiceP] position from an argument to an adjunct, besides the embedded transitive lexical verb losing the ability to assign Accusative Case. The so-called animacy restriction on the Nom-marked subject a noun phrase (NP) in –eykey passives is ascribed to the requirement that it takes the Causer/Experiencer role in –eykey passives. In contrast, –ey uyhay passives are derived from the null passive morphology attached to the matrix causative verb complex, thus the matrix Causer/Experiencer subject being demoted and realized with the particle –ey uyhay.